Development of A Parametric Cost Estimation Model for Landfill Construction Projects - Nurhayati Junaedi; Ridho Bayuaji; Alfred Jonathan Susilo (Advance Sustainable Science Engineering and Technology, 2025)
Indonesia’s waste management system is still dominated by the collect–transport–dispose approach, making landfills crucial for environmental sustainability. Landfill construction is a complex process requiring accurate cost estimation to prevent overruns and delays. This study develops a landfill construction cost estimation model using the Cost Significant Model (CSM) approach. Data were obtained from landfill project budgets in Java, Indonesia (2013–2021) and analyzed using multiple linear regression in SPSS. Results show that landfill block, leachate treatment installation, and operational road are the most significant cost components, the estimation model is Y = 3698103502.04 + 1.301X3 + 0.371X4 + 1.236X5. The model falls within the class 4 cost estimation accuracy range according to AACE International standards, making it suitable for feasibility study use. This study introduces a model, context-specific cost estimation model for landfill projects in Indonesia, supporting effective planning and sustainable infrastructure development